(untitled) (American Journal of Business Management, Economics and Banking, 2025)
This study explores the interplay between entrepreneurial skills and employee job performance within family businesses in Yenagoa, Bayelsa State, a region where such enterprises are vital to economic stability despite an oil-dominated economy. Drawing on the Resource-Based View (RBV) framework, the research examines how key entrepreneurial competencies decision-making, communication, and leadership influence workforce productivity and efficiency. Family businesses in Yenagoa face unique challenges, including informality, limited resources, and familial dynamics, which may hinder the effective application of these skills. Through a conceptual analysis, this study highlights how cultivating these skills can enhance employee performance, offering practical strategies for business owners and policymakers to strengthen these firms’ sustainability. By addressing a research gap in Yenagoa’s informal business context, the findings provide a foundation for empirical studies and contribute to understanding workforce dynamics in family-run enterprises.